كسر أفق التوقع في قصة موسى عليه السلام من القرآن الكريم - معوش, محمد الصديق; سعادة, آمنة; سعادة, فاطمة الزهراء (University of Eloued جامعة الوادي, 2024)
يحاول هذا البحث تتبع تمثلات كسر أفق التوقع في قصة موسى عليه السلام كما وردت في القرآن الكريم فجاء الموضوع ب: عنوان: "كسر أفق التوقع في قصة موسى عليه السلام من القرآن الكريم مقاربة جمالية في ضوء جماليات التلقي ". ولقد تم تسليط الضوء في هذه الدراسة على ابراز الملامح الأساسية لنظرية التلقي في أصولها الغربية مستحضرين الأسس الفلسفية المؤثرة فيها وكذا المفاهيم الإجرائية التي جاء بها كل من هانز روبرت ياوس وفولفغانغ آيزر رائدا هذه النظرية، من بين تلك المفاهيم مفهوم كسر أفق التوقع وهي الخيبة التي يحدثها النص في القارئ وعليه تبرز جمالية النصوص، وكذا ماهية القصص القرآني وخصائصه، معتمدين تقنية الوصف والتحليل، والمنهج التأويلي في الفصل الثاني لما تحمله القصة من انعطافات لفظية وسردية كسرت أفق توقع القارئ، تاركة فيه شغف البحث عن أبعادها الدلالية وفي نفسه الأثر الجمالي. from the Holy Qur'an. An aesthetic approach in light of the aesthetics of reception. The light was highlighted in this study on highlighting the basic features of reception theory in its Arabic origins, recalling the philosophical foundations that influence it, as well as the procedural concepts that were brought by Hanser Robert Jauss and Wolfgang Iser, pioneers of this theory. Among those concepts is the concept of breaking the expectation of horizon , which is the disappointment that the text causes in the reader, and thus the aesthetics of the texts are highlighted, as well as the nature of Qur'anic stories and their characteristics, adopting the technique of description and analysis, and the interpretive approach in the second chapter because of the verbal and narrative turns the story carries that break the reader's expectation of horizon , leaving in him the passion of searching for its semantic dimensions. It has an aesthetic effect in itself.
مقابلة نقدية في ضوء جماليات التلقي
نقد عربي حديث ومعاصر
Keywords: نظرية التلقي، هانز روبرت ياوس، كسر أفق التوقع، القصص القرآني، موسى عليه السلام.; Reception Theory; Hans Robert Jauss; Breaking the Horizon of Expectation; Quranic Stories; Moses; peace be upon him.